Coastal Deformation Patterns Along the Nicoya Seismic Gap, Pacific Coast, Costa Rica, Central America - Marshall, Jean S. (2004)
Summary of the paper "Coastal Deformation Patterns Along the Nicoya Seismic Gap, Pacific Coast, Costa Rica, Central America"